The Effect of Domestic Investment, Foreign Investment, Poverty, and Open Unemployment on Economic Growth in 10 Provinces of Indonesia, 2018–2022 - Dhiya Laili Izdihar; Neli Aida (International Journal of Economics, Business and Innovation Research, 2025)
This study analyzes the effects of Domestic Investment (PMDN), Foreign Investment (PMA), poverty, and open unemployment on economic growth in 10 provinces in Indonesia from 2018 to 2022. Secondary panel data were used, collected from the Central Bureau of Statistics (BPS). The method employed is panel data regression using the Fixed Effect Model (FEM), chosen based on results of Chow and Hausman tests.The results show that Domestic Investment has a negative and significant effect on economic growth, while Foreign Investment has a positive and significant effect. Poverty and open unemployment both have negative and significant effects. Simultaneously, all independent variables significantly influence economic growth with an R² of 0.6455. These findings underscore the importance of optimizing domestic investment allocation, improving the quality of foreign investment, and implementing policies for poverty alleviation and job creation to support sustainable economic growth.